Risk of bias tools in systematic reviews of health interventions: an analysis of PROSPERO-registered protocols - Farrah, Kelly; Young, Kelsey; Tunis, Matthew C; Zhao, Linlu (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Systematic reviews of health interventions are increasingly incorporating evidence outside of randomized controlled trials (RCT). While non-randomized study (NRS) types may be more prone to bias compared to RCT, the tools used to evaluate risk of bias (RoB) in NRS are less straightforward and no gold standard tool exists. The objective of this study was to evaluate the planned use of RoB tools in systematic reviews of health interventions, specifically for reviews that planned to incorporate evidence from RCT and/or NRS. Methods We evaluated a random sample of non-Cochrane protocols for systematic reviews of interventions registered in PROSPERO between January 1 and October 12, 2018. For each protocol, we extracted data on the types of studies to be included (RCT and/or NRS) as well as the name and number of RoB tools planned to be used according to study design. We then conducted a longitudinal analysis of the most commonly reported tools in the random sample. Using keywords and name variants for each tool, we searched PROSPERO records by year since the inception of the database (2011 to December 7, 2018), restricting the keyword search to the “Risk of bias (quality) assessment” field. Results In total, 471 randomly sampled PROSPERO protocols from 2018 were included in the analysis. About two-thirds (63%) of these planned to include NRS, while 37% restricted study design to RCT or quasi-RCT. Over half of the protocols that planned to include NRS listed only a single RoB tool, most frequently the Cochrane RoB Tool. The Newcastle-Ottawa Scale and ROBINS-I were the most commonly reported tools for NRS (39% and 33% respectively) for systematic reviews that planned to use multiple RoB tools. Looking at trends over time, the planned use of the Cochrane RoB Tool and ROBINS-I seems to be increasing. Conclusions While RoB tool selection for RCT was consistent, with the Cochrane RoB Tool being the most frequently reported in PROSPERO protocols, RoB tools for NRS varied widely. Results suggest a need for more education and awareness on the appropriate use of RoB tools for NRS. Given the heterogeneity of study designs comprising NRS, multiple RoB tools tailored to specific designs may be required.